Efektifitas Terapi Akupresure Terhadap Disminore pada Remaja Putri di SMPN 62 Tanjung Buntung Kota Batam Tahun 2024 - Leni Hayati; Norma Jeepi Margiyanti; Nahrul Hayat (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Background: Dysmenorrhea is abdominal pain originating from uterine cramps and occurring during menstruation due to the shedding of the endometrium. Acupressure therapy can increase the release of endorphins, thereby lowering the pain threshold. Untreated pain can negatively impact adolescent productivity, including academic performance, and disrupt daily activities. Objective: to determine the effectiveness of acupressure therapy on dysmenorrhea pain that occurs in adolescent girls. Method: This type of research used a Pre-Experimental with a One Group Pretest Posttest Design. The sample of this study consisted of 16 female adolescents with dysmenorrhea. Results: Shows a decrease in the level of dysmenorrhea pain scale before and after acupressure therapy. Before acupressure therapy, 3 respondents (8.8%) had mild pain, 10 respondents (62.5%) had moderate pain, and 3 respondents (18.8%) had severe pain. After acupressure therapy, there was a decrease in the level of pain, namely 6 (37.5%) respondents with no pain scale, 8 respondents (50%) had mild pain, and 2 respondents (18.8) had moderate pain. With the mean value before acupressure therapy was (5.31), then there was a decrease in the mean after acupressure therapy intervention for 3 days to (1.44). Based on the output of the Paired Sample T-test statistical test, the significance result was p-value = 0.000. Conclusion: There is effectiveness of acupressure therapy for dysmenorrhea in female adolescents at SMPN 62 Tanjung Buntung, Batam City in 2024.